Stellar atmospheric parameters of FGK-type stars from high-resolution optical and near-infrared CARMENES spectra - Marfil, Emilio; Tabernero, H. M.; Montes, D.; Caballero, J. A.; Soto, M. G.; González Hernández, J. I.; Kaminski, Adrian; Nagel, E.; Jeffers, S. V.; Reiners, A.; Ribas, I.; Quirrenbach, Andreas; et al. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. With the purpose of assessing classic spectroscopic methods on high-resolution and high signal-to-noise ratio spectra in the near-infrared wavelength
Gesehen am 25.02.2020